Kajian Awal : Respon Eksplan Nodus dalam Inisiasi Tunas Mikro Tanaman Karet (Hevea brasiliensis Muell. Arg.) dalam Medium WPM - Lidya Sundari; Luthfi A. M. Siregar; Diana Sofiah Hanafiah (Jurnal Agroekoteknologi, 2015)
The objective of the research was to determine the best medium for micro shoot induction of rubbertree from node explant in WPM medium with combination of Benzylamino purine (BAP) andNaphthalane-acetic acid (NAA). The research was conducted in Microcutting Laboratory,PT. Perkebunan Nusantara III Tebing Tinggi Sumatera Utara Medan from Februari 2014-Juni 2014,used complete random design with sixteen treathments and fifteen replications.The result showedthat combination BAP and NAA in WPM gave significantly different on percent of explant formingshoot. Meanwhile, for parameter life explant combination concentrated BAP and NAA showed nosignificantly different.Keywords: rubber, micro shoot, BAP, NAA, WPM